105:oral Clinical priority setting during the COVID-19-pandemic – Norwegian doctors' experiences. (28th April 2022) - Bringedal, Berit; Bååthe, Fredrik; Rø, Karin Isaksson; Miljeteig, Ingrid; Magelssen, Morten
Abstract : Introduction: Although Norway had lower infection rates and fewer patients hospitalized during the first year of the covid-19 pandemic, measures taken to avoid anticipated pressure on health care involved hard priorities of patients and staff. How did doctors experience this situation? We studied doctors' knowledge about, and adherence to, guidelines and regulations on priority setting, and whether the actual priorities were considered reasonable and justifiable. Method: 2316 members of a representative panel of doctors practicing in Norway received a questionnaire in December 2020. Data were analysed by descriptive statistics and regression analyses. Results: 1617 of 2316 (70%) responded. A majority reported familiarity with the official priority criteria, but not with the particular legislation on priority setting (the Priority Regulation/Prioriteringsforskriften), or the Directorate of Health's Guidelines for priority setting during the pandemic. 60-74% did not use guidelines for priority setting. 60, 5% experienced that some of their patients got lower priority for treatment. Of these, 47% considered this medically indefensible to some/a large extent. We saw a significant difference between GPs, hospital doctors and private specialists in considering the lower priority indefensible: 42, 6% (hospital doctors), and 57, 8% (GPs). Regression analysis showed that increased age involved fewer claims of lower priority, controlling for age and workplace, while working in primary care increased the probability of considering the priorities medically indefensible, controlling for age and gender. Discussion: If priority setting in clinical practice is to proceed in accordance with priority setting principles and guidelines, doctors' familiarity with them must improve. Apparently, the clinical priority setting in response to the pandemic was considered medically indefensible by many doctors. One interpretation is that doctors have judged that the rationing of care went too far; another is that the society, including politicians, patients, and doctors, find it hard to accept rationing of care for particular patient groups.